Climbing Higher : Toward a Middle-Income Nepal - Cosic, Damir (World Bank, Washington, DC, 2017)
Nepal's recent history of development is marred by a paradox. Many countries in the world have experienced rapid growth but modest poverty reduction, as income has increasingly concentrated in the hands of the wealthy. Nepal, however, has the opposite problem-modest growth but brisk poverty reduction. The country has halved the poverty rate in just seven years and witnessed an equally significant decline in income inequality. Yet, Nepal remains one of the poorest and slowest-growing economies in Asia, with its per capita income rapidly falling behind its regional peers and unable to achieve its long-standing ambition to graduate from low-income status.